2003
DOI: 10.1080/1606635031000141094
|View full text |Cite
|
Sign up to set email alerts
|

Untreated Heavy Drinkers: a Qualitative and Quantitative Study of Dependence and Readiness to Change

Abstract: The Birmingham Untreated Heavy Drinkers (BUHD) project recruited 500 untreated heavy drinkers directly from the community. All participants completed the Leeds Dependence Questionnaire (LDQ) and the Readiness to Change Questionnaire (RCQ) and two sub-samples of 25 participants each were interviewed in depth about their experiences of dependence and readiness to change. Quantitative and qualitative data were used to make comparisons with previous research, evaluate the applicability of pre-existing theory and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The average units reported in the previous week was 86, and most had positive scores for contemplation of change on the Readiness to Change Questionnaire (Heather and Rollnick, 1993). Finally, this letter gives us an opportunity to point out an error in our original paper (Hartney et al, 2003): in the centre of Figure 1 (p. 329) the figures should be 9 (1.8%), consistent with those in Table IX …”
mentioning
confidence: 63%
“…The average units reported in the previous week was 86, and most had positive scores for contemplation of change on the Readiness to Change Questionnaire (Heather and Rollnick, 1993). Finally, this letter gives us an opportunity to point out an error in our original paper (Hartney et al, 2003): in the centre of Figure 1 (p. 329) the figures should be 9 (1.8%), consistent with those in Table IX …”
mentioning
confidence: 63%
“…These authors identified the following stages of change: precontemplation, contemplation, preparation, action, maintenance, and relapse and recycling. Research has validated the existence of these various stages in clients presenting to addictions treatment facilities or in community samples (Demmel, Beck, Richter, & Reker, 2004;Hartney et al, 2003), as well as the success of this model in adapting treatments for addictions and compulsive behavior (Armitage, 2006;Berman, Forsberg, Durbeej, Kallman, & Hermansson, 2010;DiClemente, Schlundt, & Gemmell, 2004;Giovazolias & Davis, 2005;Mitchell & Angelone, 2006;Wade, Frayne, Edwards, Robertson, & Gilchrist, 2009). …”
Section: Desensitization Of Triggers and Urge Reprocessingmentioning
confidence: 95%
“…The 10 items map onto the ICD-10 and DSM-IV criteria for substance dependence: Pre-occupation, salience, compulsion to start, planning, maximizing effect, narrowing of repertoire, compulsion to continue, primacy of effect, constancy of state, and cognitive set. The measure has established psychometric properties with adult alcohol or opiate using samples (Hartney et al, 2003; Heather et al, 2001; Raistrick et al, 1994), primarily alcohol using young adults (Lennings, 1999; Thomas & McCambridge, 2008), and substance using adolescents (Lennings, 1999). …”
Section: Methodsmentioning
confidence: 99%
“…A more recent study with a web-based/online, low severity sample (LDQ M = 4.3) of adolescent and young adult alcohol users (ages 16–24) revealed high internal consistency and a single principal component accounting for the majority of the variance (Thomas & McCambridge, 2008). Finally, a sample of low severity (LDQ M=7.3) untreated heavy drinkers (N = 500, M age 37) yielded a two factor solution, a “drinking ideation” factor, and a “achieving and maintaining intoxication” factor (Hartney et al, 2003). …”
mentioning
confidence: 99%